ЖОҚАРЫ ОҚЫЎ ОРЫНЛАРЫНДА “ДЕНЕ ТӘРБИЯСЫ ГИГИЕНАСЫ” ПӘНИНИҢ ТУТҚАН ОРНЫ ҲӘМ ТИЙКАРҒЫ БАҒДАРЛАРЫ - Утепбергенов, А.Қ.; Мамутов, П.Ж. (FAN va JAMIYAT, 2021)
The article is devoted to the improvement of the system of training and scientific training in the field of physical culture and sports, education of a versatile and physically developed person with a high culture in the country, as well as biologically active additives, nutrients and nutrients in the diet of athletes. There is a wide understanding of good nutrition.